Workshop Comunicar Ciência - Nunes, Maria de Fátima (2020)
This workshop is part of the European Researchers Night Project (2018-2019), whose theme and practice are guided by “Science in the City”. Overcoming the barriers of laboratories and research centers and bringing science into the public space brings challenges for researchers and public. The squares, streets, libraries and museums are open to the entire population, from kids to seniors.